Awareness and practice of family planning services among married women of reproductive age in a rural municipality of Saptari district, Nepal (Journal of Patan Academy of Health Sciences, 2019)
Introductions: Unwanted pregnancies and maternal deaths can be avoided by use of family planning (FP) services. Use of modern methods of contraceptive among married women age 15-49 years in Nepal is 43%. Generally, fertility is higher among women in rural areas than in urban. This study aims to assess the awareness and practice of FP services among married women of reproductive age in a Rural Municipality of Saptari district, Nepal. Methods: Cross-sectional study with two stage sampling technique through face-to-face interview using structured questionnaire interview schedule in local language, Maithili, was done to find out awareness and practice regarding FP services in married women of 15-49 years in a Municipality of Saptari district, province 2, Nepal, from April 2018 to March 2019. Descriptive and inferential data analysis done using SPSS version16.0 software. Results: Out of 280 respondents, 257 (91.78%) had adequate awareness regarding FP services, 167 (59.64%) were current FP users, 125 (74.85%) practiced female sterilization and 39 (23.35%) used temporary methods. Common reason for not using temporary FP methods included side effects 103 (90%). Level of awareness regarding FP services was not significantly associated with their practices. Conclusions: Majority of respondents had adequate awareness regarding family planning services but FP practice was low.